Polscy imigranci we Włoszech. Trendy migracyjne, rynek pracy i system zabezpieczenia społecznego przed i po 1 maja 2004 r. - Kamila Kowalska-Angelelli (University of Warsaw, Centre of Migration Research (CMR), 2007)
– The following report is an attempt at analysing the situation of Polish immigrants on the Italian labour market prior to and after Poland's accession to the European Union. The relatively short period that has elapsed since May 1st 2004 and, consequently, a scarce number of materials and sources which could provide evidence for the possible existence of changes in migration trends in Italy, are undoubtedly a significant barrier to research on the subject matter. At the same time, however, it would be difficult to fail to notice the conspicuous changes which have taken place towards Polish immigrants in Italy after accession, both of legal-administrative nature, as well as regarding the reality of the labour market. In order to acknowledge that such changes have taken place, the author of this report carried out qualitative research among Polish immigrants working in the area of the whole Apennine Peninsula. Both specific life-histories of Poles arriving to Italy prior to and after May 1st 2004, and their perception of the possible changes connected with the reality of stay and everyday as well as professional life have been analysed. Moreover, in order to complete the picture of this new migratory situation, various legal and strictly bureaucratic issues connected with the recent alteration of Poles in Italy from 'immigrants from third countries' into 'European Union citizens' have been presented. In the course of the qualitative research different techniques have been applied, including general surveys, in-depth biographical interviews, interviews with experts, and participant observation.
Keywords: 330; Migranten; Polen (Personen); Arbeitsmigranten; Arbeitsmarkt; Soziale Sicherheit; EU-Mitgliedschaft; Italien